Effect of Synectics Model of Teaching in Enhancing Students’ Understanding of Abstract Concepts of Mathematics - Aftab Ahmad Khan & Nasir Mahmood, (PJDOL, 2023)
Abstract concepts of mathematics are always difficult for the students to comprehend. These concepts are a continuous source of low achievement in mathematics. A study was conducted to explore the effect of Synectics Model of teaching in enhancing understanding of abstract concept of mathematics. It was a form o